Perlocutionary Acts In The Film Bidaah Cinta: A Pragmatic Analysis Of Walids Character And Its Educational Implications - Komala Sari, Lusi; Azila, Nur; Apakama, Lusi Mgbemgasha (Pedagogi : Jurnal Pendidikan dan Pembelajaran, 2025)
This study investigates the perlocutionary acts of Walid, a central character in the Indonesian film Bid'ah Cinta. It focuses on how his utterances not only function as commands or instructions but also help build ideological and moral authority. Using a pragmatic approach based on Speech Act Theory—particularly J.L. Austin’s concept of perlocutionary acts—the research analyzes selected dialogues to identify the power dynamics and ideological messages embedded in Walid’s speech. The analysis shows that Walid’s language influences other characters psychologically and morally. It portrays him as a dominant figure who shapes beliefs and behaviors. These findings have meaningful implications for language and literature education. They highlight the value of teaching students to recognize how language in literary texts reflects and reinforces social values. Integrating film dialogue analysis into the classroom can enhance students’ pragmatic skills, critical thinking, and appreciation of context in communication.